Bimolecular reactions of CH2CN2+ with Ar, N2 and CO: reactivity and dynamics. Issue 26 (27th June 2022) - Armenta Butt, Sam; Price, Stephen D.
Abstract : Reactions between CH2 CN 2+ and Ar, N2 and CO involve competition between collision-induced dissociation, proton transfer and electron transfer. The experiments reveal that CH2 CN 2+ explores several geometries, a conclusion supported by calculations. Abstract : The reactivity, energetics and dynamics of bimolecular reactions between CH2 CN 2+ and three neutral species (Ar, N2 and CO) have been studied using a position sensitive coincidence methodology at centre-of-mass collision energies of 4.3–5.0 eV. This is the first study of bimolecular reactions involving CH2 CN 2+, a species relevant to the ionospheres of planets and satellites, including Titan. All of the collision systems investigated display two collision-induced dissociation (CID) channels, resulting in the formation of C + + CH2 N + and H + + HC2 N + . Evidence for channels involving further dissociation of the CID product HC2 N +, forming H + CCN +, were detected in the N2 and CO systems. Proton-transfer from the dication to the neutral species occurs in all three of the systems via a direct mechanism. Additionally, there are product channels resulting from single electron transfer following collisions of CH2 CN 2+ with both N2 and CO, but interestingly no electron transfer following collisions with Ar. Electronic structure calculations of the lowest energy electronic states of CH2 CN 2+ reveal six local geometric minima: both doublet and quartet spin states for cyclic, linear (CH2 CN), and linear isocyanide (CH2 NC) molecular geometries. The lowest energy electronic state was determined to be the doublet state of the cyclic dication. The ready generation of C + ions by collision-induced dissociation suggests that the cyclic or linear isocyanide dication geometries are present in the [CH2 CN] 2+ beam.